2012
DOI: 10.1111/j.1582-4934.2011.01400.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro analyses of the anti‐fibrotic effect of SPARC silencing in human Tenon’s fibroblasts: comparisons with mitomycin C

Abstract: Failure of glaucoma filtration surgery (GFS) is commonly attributed to scarring at the surgical site. The human Tenon’s fibroblasts (HTFs) are considered the major cell type contributing to the fibrotic response. We previously showed that SPARC (secreted protein, acidic, rich in cysteine) knockout mice had improved surgical success in a murine model of GFS. To understand the mechanisms of SPARC deficiency in delaying subconjunctival fibrosis, we used the gene silencing approach to reduce SPARC expression in HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 47 publications
(57 reference statements)
4
42
0
Order By: Relevance
“…Seet et al, reported that the reduction of SPARC improved surgical success in a surgical mouse model of ocular scarring . Hence, the targeting of SPARC expression has been identified as a potential therapeutic strategy for wound modulation and reducing scarring since SPARC down‐regulation also resulted in delayed cell migration, reduced collagen contractility and lower expressions of profibrotic and pro‐inflammatory genes . Our study with LbL nanoparticles targeting SPARC protein and reducing the mRNA levels in FibroGRO cells clearly confirm a promising approach for the use of RNAi as a therapeutic strategy for minimizing fibrosis.…”
Section: Resultssupporting
confidence: 72%
“…Seet et al, reported that the reduction of SPARC improved surgical success in a surgical mouse model of ocular scarring . Hence, the targeting of SPARC expression has been identified as a potential therapeutic strategy for wound modulation and reducing scarring since SPARC down‐regulation also resulted in delayed cell migration, reduced collagen contractility and lower expressions of profibrotic and pro‐inflammatory genes . Our study with LbL nanoparticles targeting SPARC protein and reducing the mRNA levels in FibroGRO cells clearly confirm a promising approach for the use of RNAi as a therapeutic strategy for minimizing fibrosis.…”
Section: Resultssupporting
confidence: 72%
“…The elucidation of the the regulatory mechanisms of MMPs will be a milestone in the prevention and treatment of intracranial aneurysms. Combined with previous research [48], [49], the present study shows that SPARC regulates MMP-2 and MMP-9 expression in human intracranial aneurysms; however, whether SPARC is an upstream or downstream regulatory factor remains to be determined. Our results imply that SPARC may have a role in the progression of intracranial aneurysms, and this finding has great significance in explaining the pathogenesis and clinical treatment of intracranial aneurysms.…”
Section: Discussionsupporting
confidence: 77%
“…2 SPARC can also increase the expression and activity of matrix metalloproteinases (including MMP-7, MMP-3, MMP-2 and MMP-13) [48] and can reduce the level of the MMP inhibitor TIMP. After SPRAC gene knockout, the expression levels of MMP-2, MMP-9 and MMP-14 were lower [49], and MMPs can degrade biological macromolecules in extracellular matrix. Studies have confirmed that MMP activity is increased in IA patients [50], and MMPs may be involved in the formation and development of aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura et al (2004) using RNAi targeting TGF-β2 reported a significant reduction in the inflammatory response and matrix deposition in a mouse model of subconjunctival scarring. Recently, the siRNA silencing of secreted protein acidic and rich in cysteine (SPARC) has also been shown to reduce the pro-fibrotic TGF-β2 in in vitro experiments with human Tenon's fibroblasts (Seet et al, 2012). Likewise, SPARC down-regulation induced a cell migration delay, reduced collagen contractility as well as the expression of other pro-fibrotic and proinflammatory genes, which indicates that SPARC silencing has potential as an anti-fibrotic strategy.…”
mentioning
confidence: 99%